Lightweight Cryptography Techniques for MHealth Cybersecurity - Shahbodin, F; Azni, AH; Ali, T; Mohd, CKNCK (Assoc Computing Machinery, 2024)
A new integration of wireless communication technologies into the mobile heath system also known as mHealth has instigated a momentous research interest in the field of mobile security. mHealth systems are unique in terms of characteristics, challenges, architecture, and applications. Consequently, security requirements related to mHealth system are more complex as compared to mobile networks and conventional wireless networks. This article presents a survey about developments in mHealth system from the perspective of lightweight cryptographic protocols and privacy preserving algorithms. Unique characteristics of mHealth systems are presented which make the embedded security applications computationally hard as well as memory constrained. The current study also deals with the fundamental security requirements, essential for mHealth communication. Furthermore, awareness of security threats and their cryptographic solutions in terms of future health industry are discussed. In addition, lightweight cryptographic solutions are summarized. These strategies can be enhanced or incorporated all in all to meet the security perquisites of future patients' data security.